Evaluation of inherited germline mutations in cancer susceptibility genes among pancreatic cancer patients: a single-center study - Francesca Tavano; Domenica Gioffreda; Andrea Fontana; Orazio Palmieri; Annamaria Gentile; Tiziana Latiano; Anna Latiano; Tiziana Pia Latiano; Matteo Scaramuzzi; Evaristo Maiello; Francesca Bazzocchi; Francesco Perri (BMC, 2023)
Abstract Background Germline mutations in cancer susceptibility genes were identified in pancreatic cancer (PanC) patients with a sporadic disease and in those unselected for family cancer history. Methods With the aim to determine the prevalence of germline predisposition genes mutations in PanC, and to evaluate whether they were associated with the presence of PanC, we profiled a custom AmpliSeq panel of 27 cancer susceptibility genes in 47 PanC patients and 51 control subjects by using the Ion Torrent PGM system. Results Multigene panel testing identified a total of 31 variants in 27 PanC (57.4%), including variants with pathogenic/likely pathogenic effect, those of uncertain significance, and variants whose clinical significance remains currently undefined. Five patients carried more than one variant in the same gene or in different genes. Eight patients (17.0%) had at least one pathogenic/likely pathogenic variant in four main genes: CFTR (10.6%), BRCA2 (8.5%), ATM and CHEK2 (2.1%). Pathogenic/likely pathogenic mutation were identified in patients with positive PanC family history (20%) or in patients without first-degree relatives affected by PanC (13.6%). All the BRCA2 mutation carriers were unselected PanC patients. The presence of mutations in BRCA2 was significantly associated with an increased occurrence of PanC and with positive family history for endometrial cancer (p = 0.018). Conclusions This study confirmed the potential remarkable contribution of BRCA2 in assessing the presence of PanC. Overall our findings supported the recommendation of offering the germline testing to all the PanC patients with the intent to reduce the number of underdiagnosed carriers of mutations in predisposition genes, and not to preclude their relatives from the opportunity to benefit from surveillance programs.